Mathematical modeling and simulation of SEIR model for COVID-19 outbreak: A case study of Trivandrum - M, Aakash; C, Gunasundari; Al-Mdallal, Qasem M. (Frontiers in Applied Mathematics and Statistics, 2023)
In this paper, we formulated a mathematical model of COVID-19 disease with the effects of partially and fully vaccinated individuals. Here the purpose of this study is to solve the model using some numerical methods. It is complex to solve four equations of $SEIR$ model, so we introduce Euler and fourth order Runge Kutta method to solve the model. These two methods are efficient and practically well suited for solving initial value problem. We considered the capital of Kerala, Trivandrum city for the simulation. Here we study the comparison of these two methods and also we found out the differences of solutions between two methods. At last we discuss the numerical comparison between these two methods with the real world data.